PENGARUH ANGKATAN KERJA, PENDAPATAN PERKAPITA, INDEKS PEMBANGUNAN MANUSIA DAN BELANJA PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI KOTA JAMBI - Reca Aulya; Erni Achmad; Rahma Nurjanah (PT. Hasba Edukasi Mandiri, 2025)
This research aims to: 1) Describe the development of the workforce, per capita income, the human development index (HDI), government spending, and economic growth in Jambi City during the period 2005–2024. 2) Analyze the influence of the workforce, per capita income, the human development index, and government spending on the economic growth of Jambi City. The type of data used is secondary data sourced from documentation or available reports. The data used is time series data from 2005 to 2024. Data analysis used is descriptive analysis and multiple linear regression analysis. The results obtained are: 1) The development of the workforce, per capita income, HDI, government spending, and economic growth of Jambi City during 2005–2024 shows a general upward trend although accompanied by fluctuations. 2) Based on the results of the multiple linear regression analysis, the variables per capita income and government spending have a significant effect on the economic growth of Jambi City partially. Meanwhile, the variables labor force and HDI do not have a significant effect on the economic growth of Jambi City partially.